An Essence of Portfolio Planning in the Software Development Industry - Homayounfar, Payam (Istota planowania portfela w przedsiębiorstwach tworzących oprogramowanie, 2010)
Companies in the software industry are mostly fast growing organizations. Together with the fast growth comes the loss of transparency and problems with structures where projects become their own dynamic and importance, even if other projects might be more important for the customers and the company’s goals. Portfolio Planning (PP) describes the important first step of portfolio management in the software development industry. The process links the investment opportunities with the global strategy of the company. Furthermore it provides the necessary tools and taxonomy to break down the vision into small work packages that can be realized in development projects. Different roles and responsibilities are described for PP which is a highly communicative process with the necessity of cross company alignment on different levels.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 147-159
Keywords: portfolio planning; investment decisions; life cycle; corporate strategy; planning process; investment cluster